A simple method to quantify azo dyes in spices based on flow injection chromatography combined with chemometric tools - Nussbaum, Luana; Llamas, Natalia; Chocholouš, Petr; Rodríguez, María Susana; Sklenářová, Hana; Solich, Petr; Di Anibal, Carolina; Acebal, Carolina C (Journal of food science and technology, 2022)
UNLABELLED: Para Red (PR) and Sudan dyes have been illegally used as colorants to adulterate certain foods by enhancing their red/orange colour. In addition, they are toxic and carcinogenic. This work presents the development of a simple flow injection chromatographic method combined with chemometric tools to perform the determination of PR, Sudan I (SI) and Sudan II (SII) in food samples. The flow chromatographic system consisted of a low-pressure manifold coupled to a reverse phase monolithic column. A Partial Least Square (PLS) model was applied to resolve overlapped absorption spectra registered for each dye at the corresponding retention time. The relative errors of calibration (RMSECV, %) were 0.49, 0.85 and 0.23, and the relative errors of prediction (RMSEP, %) were 1.12, 0.75 and 0.33 for PR, SI and SII, respectively. The residual predictive deviation (RPD) values obtained were higher than 3.00 for all analytes. The method was successfully applied to quantify the dyes in six different commercial spices samples. The results were compared with the HPLC reference method concluding that there were no significant differences at the studied confidence level (α = 0.05). The proposed method can be used to rapidly determine the analytes in a simple, reliable, low-cost and environmentally-friendly manner. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13197-021-05299-8.
Keywords: Flow injection analysis; Spices; Food adulteration; Azo dyes; Chemometrics; Chromatography